Prime radical of Ore extensions over δ -rigid rings - Bhat, V.K. (Algebra and Discrete Mathematics, 2009)
Let R be a ring. Let σ be an automorphism of R and δ be a σ-derivation of R. We say that R is a δ-rigid ring if aδ(a)∈P(R) implies a∈P(R), a∈R; where P(R) is the prime radical of R. In this article, we find a relation between the prime radical of a δ-rigid ring R and that of R[x,σ,δ]. We generalize the result for a Noetherian Q-algebra (Q is the field of rational numbers).